Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Tentang HIV/AIDS Pada Siswa SMAN 2 Haharu Kabupaten Sumba Timur Tahun 2022 - Enggllika Remijawa; Deviarbi S. Tirra; Honey I. Ndoen (Jurnal Kesehatan, 2022)
HIV/AIDS is a disease that can attack the immune system caused by a virus and is still a concern for many people today. Hiv/AIDS knowledge in students is students’ understanding of the symptoms, causes, ways of transmission and ways of prevention. High school students are students who are growing up and are looking for their identity, such as hanging out with peers and even having relationships with the opposite sex. The purpose of this study was to analyze factors related to knowledge about HIV/AIDS in students of SMAN 2 Haharu, East Sumba Regency. This research is quantitative research with a cross-sectional approach. The population in this study was all students of SMAN 2 Haharu class X and class XI, with a total of 222 students. The sample in this study was 107 people, with a sampling technique using proportional random sampling. The analysis used in this study was univariate analysis and bivariate analysis by testing the relationship of chi square. In general, the author concludes that there are factors related to knowledge about HIV/AIDS, namely age, social, peers, dating experiences, and sources of information. The results showed that there was a relationship between knowledge and age, social, peers, dating experience and sources of information with each p-value = 0.000, but in the age variable, p-value = 0.002. The relevant government and health workers need to work together to increase knowledge about HIV / AIDS in students by implementing counseling and socialization to students of SMAN 2 Haharu.